2004
DOI: 10.1074/jbc.m310534200
|View full text |Cite
|
Sign up to set email alerts
|

Outer Pore Topology of the ECaC-TRPV5 Channel by Cysteine Scan Mutagenesis

Abstract: The substituted cysteine accessibility method (SCAM) was used to map the external vestibule and the pore region of the ECaC-TRPV5 calcium-selective channel. Cysteine residues were introduced at 44 positions from the end of S5 (Glu 515 ) to the beginning of S6 (Ala 560 ). Covalent modification by positively charged MTSET applied from the external medium significantly inhibited whole cell currents at 15/44 positions. Strongest inhibition was observed in the S5-linker to pore region (L520C, G521C, and E522C) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 42 publications
2
43
0
Order By: Relevance
“…Mutagenesis study in the pore region of TRPV1 produce functional changes in the permeation properties as expected (Garcia-Martinez et al, 2000). Cysteine accessibility experiments on a related homolog, TRPV5, support a coil structure followed by a helical segment and two distinct coiled fragments before S6 (Dodier et al, 2004). The present study also shows a close homology in the pore sequences after removal of 15 residues.…”
Section: Discussionsupporting
confidence: 75%
“…Mutagenesis study in the pore region of TRPV1 produce functional changes in the permeation properties as expected (Garcia-Martinez et al, 2000). Cysteine accessibility experiments on a related homolog, TRPV5, support a coil structure followed by a helical segment and two distinct coiled fragments before S6 (Dodier et al, 2004). The present study also shows a close homology in the pore sequences after removal of 15 residues.…”
Section: Discussionsupporting
confidence: 75%
“…[51,75]. In addition, Huang and colleagues reported that PIP 2 activates TRPV5 and that activation of the channel by PIP 2 reduces the sensitivity of TRPV5 to the inhibition by the intracellular [Mg 2+ ] [17,42]. In this model, hydrolysis of PIP 2 by receptor activation of PLC may increase the sensitivity for Mg 2+ inhibition.…”
Section: Clathrin and Caveolinmentioning
confidence: 94%
“…Oocytes were coinjected with the S556C mutant of TRPV5, with or without WNK3. A previous study showed that TRPV5 proteins with cysteine at position 556 are inhibited when oocytes are incubated with the cell-impermeable thiol reagent 2-trimethylammonium-ethyl-methanethiosulfonate bromide (MTSET; Toronto Research Chemicals, North York, Ontario, Canada) (13). The oocytes were incubated with 2 mM MTSET for 5 min, which is sufficient to irreversibly inhibit the majority of functional TRPV5 channel proteins at the oocyte surface.…”
Section: Methodsmentioning
confidence: 99%